2022
DOI: 10.3390/tropicalmed7080194
|View full text |Cite
|
Sign up to set email alerts
|

Contributory Factors to Successful Tuberculosis Treatment in Southwest Nigeria: A Cross-Sectional Study

Abstract: Tuberculosis (TB) is one of the oldest human diseases, and preventing treatment failure is critical. This is because TB cases pose a risk to the immediate and remote communities due to the potential for spread, particularly for multidrug-resistant (MDR) strains that have been associated with higher morbidity and mortality rates. Hence, this study looked at the factors that influence TB treatment outcomes in Southwest Nigeria. We conducted a cross-sectional study with 712 TB patients from 25 directly observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…Based on the results of bivariate analysis, the variable of age does not have a significant relationship with the success of TB treatment (p=0.165). These findings are consistent with the results of a study conducted in Nigeria, which also demonstrated that age groups do not have a significant relationship with the success of TB treatment [18]. It's similar to the findings of a previous study conducted at RSUD Ungaran in Kabupaten Semarang, which indicated that the age of TB patients did not have a significant relationship with the duration of treatment for TB category I until recovery [19].…”
Section: The Association Between Age and Treatment Outcome Of Drug-su...supporting
confidence: 90%
See 1 more Smart Citation
“…Based on the results of bivariate analysis, the variable of age does not have a significant relationship with the success of TB treatment (p=0.165). These findings are consistent with the results of a study conducted in Nigeria, which also demonstrated that age groups do not have a significant relationship with the success of TB treatment [18]. It's similar to the findings of a previous study conducted at RSUD Ungaran in Kabupaten Semarang, which indicated that the age of TB patients did not have a significant relationship with the duration of treatment for TB category I until recovery [19].…”
Section: The Association Between Age and Treatment Outcome Of Drug-su...supporting
confidence: 90%
“…It's similar to the findings of a previous study conducted at RSUD Ungaran in Kabupaten Semarang, which indicated that the age of TB patients did not have a significant relationship with the duration of treatment for TB category I until recovery [19]. Previous studies have indicated a similar pattern among TB patients, with the highest burden observed in the age groups ranging from young to middle-aged individuals [18]. The Drug-Susceptible TB patients who became the samples in this study were predominantly in the age group of 15-44 years, and the highest percentage of successful TB treatment was found in the age group of 15-44 years (95.2%).…”
Section: The Association Between Age and Treatment Outcome Of Drug-su...supporting
confidence: 87%
“…Cases of pulmonary TB in people with diabetes mellitus comorbidity have never been found (8). Pulmonary TB is transmitted through the air (9) when the patient sprinkles mucus or phlegm when coughing or s n e e z i n g ( 1 0 ) . D u r i n g t h i s t i m e , t h e t u b e r c u l o s i s -c a u s i n g b a c t e r i a , mycobacterium tuberculosis, also come out through the mucus and were carried into the air (11).…”
mentioning
confidence: 99%